Classification of the Lithuanian Text of Email Enquieries of an Insurance Company with a Big Number of Customer Categories - Kiaunė, Karolis; Ramanauskaitė, Simona (Jaunųjų mokslininkų darbai, 2019)
Natural language processing and classification have been widely used in English-speaking countries. However, analysis and classification of a Lithuanian text is a complex issue and has not been fully implemented. This is due to complexity and peculiarities of the Lithuanian language, so methods appropriate for other languages, are not always appropriate for the Lithuanian language.Three selected word processing options and their various combinations were used and it was assessed how different and consistent text classification methods are able to classify insurance company customers‘ enquiries sent by email. This study is unique because a great number of methods were used and classification accuracy of a Lithuanian text in a large number of categories (33) was further assessed.Natural language processing problems, analogous studies of Lithuanian text classification were analyzed, research methodology was proposed and research findings were discussed in the paper.
Keywords: NLP; text classification; emails; text processing